Impact Of Celebrity Endorsement Advertisement On Consumers - Thakur, Ms. Sarima (The journal of contemporary issues in business and government, 2021)
Advertisement plays important role within the present era of data explosion. Celebrity endorsement may be a channel during which a star acts as a spokesperson of the brand. Celebrities performances give spectacular results when shaping the common opinion because people have faith in their favourites. Celebrity may be a generic name for the person from any field of popular industry like filmmaking, sports, politics, social life, science, or theatre with some extraordinary results of excellent cause and positive value. In ever growing competitive market Celebrities testimonial and advice are the best tool available for marketing. The celebrity Endorsement creates the best impact in the global market for building brand reputation. This research paper specifically discusses about how endorsement of product by celebrity effect consumers’ purchasing decisions.